Pengaruh Penjarangan Beri terhadap Kualitas Buah Anggur (Vitis vinifera L.) Varietas Prabu Bestari - SARI, NI KETUT KARINA; SUKEWIJAYA, I MADE; GUNADI, I GUSTI ALIT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Effect of Thinning Berries on quality of Grapes ( Vitis Vinifera L.) Prabu Bestari Variety The Prabu Bestari grape variety is an introduced grape from Australia which has been assembled by the Research Institute for Citrus and Subtropical Fruits (Balitjestro – Malang) through selection, this Prabu Bestari variety is a variety that was released in December 2006.  This experiment studys the effect of berry thinning on the quality of Prabu Bestari grapes. This research was conducted from October 2020 – January 2021. This research was conducted at the Experimental Garden of the Faculty of Agriculture (KPFP) Jl. Pulau Moyo No. 16X, Pedungan, Denpasar, Bali, at an altitude of 9-10 meters above sea level. This study used a randomized block design (RBD). The treatments tested were berry thinning consisting of 4 levels, Control (P 0 ), 10%-25% berry thinning (P 1 ), berry thinning > 25%-40% (P 2 ), berry thinning >40%-55 % (P 3 ). The experiment was repeated 6 times, each treatment using 2 experimental units, so that there were 48 experimental units of bunch samples. The berry thinning treatment had a very significant effect on the variables of bunch weight per bunch, berry weight, vitamin C content, total dissolved solids, and total titrated acid, and a significant effect on the variable diameter of berries, but had no significant effect on the variables of bunch length and tannin content. The results of statistical analysis using the LSD, test of berry thinning with P3 were able to increase fruit weight per bunch by 19.9% ??compared to control, berry diameter 21.37 mm, berry weight 7.93 g, total soluble solids 7.97 o Brix, total acid titrated 1.21%.